Agrármodellek társadalmi, gazdasági és környezeti hatásai - Buday-Sántha, Attila (Közép-Európai Közlemények, 2010)
To summarise, we can state that, to shape an area suitable for society, for an increasing population and for biological–technical–technological development which can cope smoothly with evolving market requirements, constant change is necessary – as is development in agricultural production. A significant feature of this evolutionary process is that the problem of sustaining the population has to be solved in an environment of decline – both in terms of the land available and in the agricultural workforce – although at a cost acceptable to the market. Agricultural production needs to be developed simultaneously, but by using continuously shrinking natural resources and with the increasing utilisation of capital. The results of this development are to be seen in increased efficiency – in the productivity of both land and labour and in the improving ratio of the numbers of agricultural workers to the population which they feed. This development process can basically be traced over 100 years of Hungarian agriculture.